Impact of contaminant size and density on their incorporation into sea ice - Alice Pradel; Rudolf Hufenus; Martin Schneebeli; Denise M. Mitrano (Nature Communications)
Abstract Sea ice accumulates contaminants and redistributes them laterally as the ice drifts and vertically as it melts. Contaminant incorporation into sea ice must be better understood to resolve contaminant cycling and exposure to polar organisms. Here we develop an experimental method that mimics the formation of young sea ice and enables the quantification of model contaminants separately in the ice matrix and brine. Several limitations inherent in field studies are overcome using this approach. Results show that dissolved contaminants (<1 nm) and dispersed colloidal contaminants (1 nm–1 μm) follow the same behavior as sea salts. When colloids aggregate they follow a similar transport pathway to high-density particulate contaminants (>1 μm). While high-density particles are depleted in sea ice and low-density particles are enriched relative to their initial concentration in seawater, both are engulfed and can travel in wide brine channels. These results can also help to predict the incorporation of natural species in sea ice.